HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU DENGAN KEJADIAN TINEA IMBRIKATA DI DESA TELUK PONGKAL KECAMATAN SOKAN KABUPATEN MELAWI TAHUN 2013 - ., Yohanes Filem (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Tinea imbrikata (Lusung) are found in the tropics and usuallyattacking tribes. It is important to know how Tinea Imbriakta (Lusung) mayoccur and how it relates to knowledge, attitudes and behaviors. Objective:This study is aimed to obtain the level of knowledge, attitudes and behaviorand to determine the characteristics of patients with Tinea Imbrikata and itsrelation between knowledge, attitudes and behaviors on the incidence ofTinea Imbrikata in Bay Village Pongkal Sokan Melawi District in 2013.Methods: This study is an observational analytic study with cross sectionalapproach. The research was conducted in the village of Bay District PongkalSokan, Melawi in April-May 2013. Data were taken from 100 respondents.Data were analyzed using comparative analysis through Chi square test.Results: The majority of respondents had knowledge, attitude and badbehavior on the incidence of Tinea Imbrikata. As many as 63% ofrespondents had poor knowledge of the Tinea Imbrikata. As many as 67% ofrespondents had bad attitude. As many as 57% of respondents had Tineaimbrikata had bad behavior. There is a significant relationship betweenknowledge and attitudes towards Tinea Imbrikata events (p = 0.000). There isa significant relationship between knowledge and behavior towards imbrikatacapitis (P = 0.000). There is a significant association between attitudes andbehavior towards Tinea imbrikata events (p = 0.000). Conclusion: There is asignificant relationship between knowledge, attitudes and behaviors on theincidence of Tinea Imbrikata (Lusung) in the village of Bay District PongkalSokan Melawi.Keywords: Knowledge, Attitude, Behavior, Tinea Imbrikata